Foreign Direct Investment: International Strategies by Business Groups - Pelayo Maciel, Jorge; Ortiz Barrera, Manuel Alfredo; Pérez Esparza, Aimee (Mercados y Negocios, 2018)
This research analyses the decision of foreign direct investment (FDI) followed by business groups, identifies two forms: acquisition and minority purchase of foreign company shares. Analyses how it affects the performance of such groups. Also includes the concentration of property since it forms part of corporate governance. In order to achieve this, a data panel analysis with information of 39 business groups and a total of 3,443 subsidiaries and that have also made FDI in a period ranging from 2012 to 2015. The findings were that the minority purchase of shares achieves a positive relationship with performance and clearly shows that the company's concentrated ownership has a negative relation to performance.